COVID-19 Vaccination in Autoimmune Patients: A Literature Review - Wardhany, Atiqah Nurul; Awalia; Setiabudi, Rebekah J (Universitas Airlangga, 2024)
Patients with autoimmune diseases, especially rheumatic diseases, have their own concerns regarding the coronavirus disease 2019 (COVID-19) vaccination. Their concerns are specifically related to the physicological response, side effects, and effectiveness of the COVID-19 vaccination. COVID-19 and autoimmune diseases share some similarities in their clinical manifestations, immune responses, and pathogenic mechanisms. The correlation between COVID-19 vaccination and autoimmune diseases can be attributed to epitope mimicry, where the antigen contained in the vaccine has a structural similarity to self-antigen. The purpose of this literature review was to discuss the various types of vaccines, the side effects of the COVID-19 vaccination, and the effect of autoimmune patients' medication on the administration of the COVID-19 vaccination. According to several articles obtained in this study, most autoimmune patients typically experienced mild to moderate side effects. It was not advised for these patients to stop treatment before receiving the COVID-19 vaccination, as doing so was unlikely to affect the vaccine's effectiveness or the patients' immune response. The condition of the autoimmune patients was what influenced the immune response mediated by antibodies. Therefore, the COVID-19 vaccination must be administered when the patients are in a stable condition. In conclusion, it was determined that there is no restriction preventing autoimmune patients from receiving the COVID-19 vaccination. However, it should be noted that autoimmune patients are not recommended to receive live vaccines. Highlights: 1. This study reviewed the concerns of autoimmune patients over the side effects of the COVID-19 vaccination on their prescribed medication. 2. It is advisable for autoimmune patients to refrain from obtaining live-attenuated vaccines because of their potential effect on the immune response.